Human minds and animal stories : how narratives make us care about other species /: how narratives make us care about other species. (2019) - (Professor of literary theory), Małecki, Wojciech; Sorokowski, Piotr; Pawlowski, Boguslaw; Cieński, Marcin
No abstract available